Microwave Spectroscopic and Atoms in Molecules Theoretical Investigations on the Ar⋅⋅⋅Propargyl Alcohol Complex: Ar⋅⋅⋅HO, Ar⋅⋅⋅π, and Ar⋅⋅⋅C Interactions. Issue 4 (6th January 2013) - Mani, Devendra; Arunan, Elangannan
Abstract The structure of the Ar⋅⋅⋅propargyl alcohol (Ar⋅⋅⋅PA) complex is determined from the rotational spectra of the parent complex and its two deuterated isotopologues, namely Ar⋅⋅⋅PA‐D(OD) and Ar⋅⋅⋅PA‐D(CD). The spectra confirm a geometry in which PA exists in the gauche form with Ar located in between OH and CCH groups. All a, b and c types of transitions show small splitting due to some large‐amplitude motion dominated by COH torsion, as in the monomer. Splittings in a‐ and b‐type transitions are of the order of a few kilohertz, whereas splitting in the c‐type transitions is relatively larger (0.9–2.6 MHz) and decreases in the order Ar⋅⋅⋅PA>Ar⋅⋅⋅PA‐D(CD)>Ar⋅⋅⋅PA‐D(OD). The assignments are well supported by ab initio calculations. Atoms in molecules (AIM) and electrostatic potential calculations are used to explore the nature of the interactions in this complex. AIM calculations not only reveal the expected OH⋅⋅⋅Ar and π⋅⋅⋅Ar interactions in the Ar⋅⋅⋅gauche‐PA complex, but also novel C⋅⋅⋅Ar (of CH2OH group) and OH⋅⋅⋅Ar interactions in the Ar⋅⋅⋅trans‐PA complex. Similar interactions are also present in the Ar⋅⋅⋅methanol complex.